Women-Led Startups In India: Funding Schemes and Challenges (Trinity Journal of Management, IT & Media (TJMITM), 2022)
Nowadays the increasing presence of women as entrepreneurs in India has led to the significant impact on the economic growth and social development of the country. Women are not only managing home and work together, but also making a significant contribution to the economic development of the economy. As per the sixth economic census, by the Ministry of Statistics and Programme Implementation (MoSPI), women constitute around 13.76% of the total entrepreneurs in India and account for 17 percent of GDP in India. The government, recognizing the potential of start-ups, particularly those led by women, is also taking so many steps to accelerate their growth. Different policies and schemes like Start-up India have been initiated for sustainable growth of women startups and to promote a balanced growth in the country. The present study is an attempt to explore the sources and schemes of financial assistance for women-led startups in India and to analyze the different challenges faced by women as an entrepreneur in India. The secondary data collected from reports, journals, databases, websites, magazines, etc have been used for this study. This study will enable young entrepreneurs, students and researchers to understand the present funding opportunities and challenges for women entrepreneurs in India.
Keywords: Women-led startups; Women entrepreneur; Funding schemes; Economic growth; Challenges